The - edited by Michael Gallagher and Paul Mitchell (Oxford University Press, 2005)
The book provides detailed analyses of the operation of a diverse set of electoral systems in their national context. Each chapter explains how the electoral system really works in the given country, examining the strategic incentives the system provides to voters, candidates, and parties. All country chapters have a common format and structure. Successive sections analyze: the institutional context; how each electoral system was chosen historically; how the current electoral system operates (the rules, mechanics, and ballot structure); and the political consequences of the current system (the impact on the party system, the internal life of parties, and the impact on parliament and government formation). Each country chapter then contains a final section which focuses on the politicization of electoral institutions. In recent years many countries have changed their electoral systems, either entirely or in part so there is a strong focus on the processes of electoral reform, both historically and prospectively. The book concentrates on the real world 'politics', as well as the 'political science' of electoral systems